Reference scheme reduction on subtypes in ORM - Carver, Andy (Springer Berlin Heidelberg, 2013)
Object-Role Modeling (ORM) allows composite reference schemes for object types to be portrayed using either objectification (in the sense of situational nominalization) or coreference (as defined in ORM rather than linguistics). In practical modeling, cases can arise where a subtype of a compositely identified object type has a natural reference scheme that utilizes only some components of the supertype’s reference scheme. Using the supertype’s reference scheme to verbalize facts for the subtype then leads to redundancy or other irrelevance in the verbalization. Moreover, if such cases are input directly to the ORM’s standard relational mapping procedure (Rmap), this can lead to table schemes that are not fully normalized. The paper identifies ways in which such problems can arise, and proposes ways to avoid these problems, partly by extending earlier work on reference scheme reduction, role redirection, and disjunctive reference, illustrating the approach with some practical examples.